Regulating the Inner Helmholtz Plane for Stable Solid Electrolyte Interphase on Lithium Metal Anodes - Yan, Chong; Li, Hao-Ran; Chen, Xiang; Zhang, Xue-Qiang; Cheng, Xin-Bing; Xu, Rui; Huang, Jia-Qi; Zhang, Qiang (Journal of the American Chemical Society, 2019)
The stability of a battery is strongly dependent on the feature of solid electrolyte interphase (SEI). The electrical double layer forms prior to the formation of SEI at the interface between the Li metal anode and the electrolyte. The fundamental understanding on the regulation of the SEI structure and stability on Li surface through the structure of the electrical double layer is highly necessary for safe batteries. Herein, the interfacial chemistry of the SEI is correlated with the initial Li surface adsorption electrical double layer at the nanoscale through theoretical and experimental analysis. Under the premise of the constant solvation sheath structure of Li+ in bulk electrolyte, a trace amount of lithium nitrate (LiNO3) and copper fluoride (CuF2) were employed in electrolytes to build robust electric double layer structures on a Li metal surface. The distinct results were achieved with the initial competitive adsorption of bis(fluorosulfonyl)imide ion (FSI–), fluoride ion (F–), and nitrate ion (NO3 –) in the inner Helmholtz plane. As a result, Cu–NO3 – complexes are preferentially adsorbed and reduced to form the SEI. The modified Li metal electrode can achieve an average Coulombic efficiency of 99.5% over 500 cycles, enabling a long lifespan and high capacity retention of practical rechargeable batteries. The as-proposed mechanism bridges the gap between Li+ solvation and the adsorption about the electrode interface formation in a working battery.